La retirada de Contenidos Ilícitos por los prestadores de servicios en línea - Moreno Blesa, Lidia (2021)
The irruption of the internet in a globalized world brings great advantages in the commercial and business sector. However, this new reality also has a strong social impact within the sphere of people’s privacy, especially when it comes to social networks This article explores the Judgement of Eva Glawischnig-Piesczek against Facebook Ireland Limited of the Court of Justice of the European Union case, in order to identify the extent to which online service providers are liable for illegal content that is shared on their websites. To accomplish this, the author debates if Facebook is a data hosting service provider to which the European Union regulations can be applied and what liability regime would be applicable to it for the broadcast of illegal content within their website. After that, she reviews the international judicial competence and the applicable law in the face of the violation of personal rights due to the dissemination of these contents. Finally, she reviews the territorial scope that an obligation to remove this type of content imposes.